(untitled) (Marketing Journal, 2025)
The article provides a comprehensive assessment of the impact of family entrepreneurship on poverty reduction in Namangan region through multi -factor econometric analysis. The study explores the relationship between indicators of family business developmen t, employment dynamics, household income levels, credit expansion, and demographic factors over the period 2015 –2024. By applying econometric techniques such as OLS, fixed and random effects models, instrumental variables, and robust standard errors, the r esearch identifies the intensity of the causal № 1 635 linkage between family entrepreneurship activities and the reduction of poverty.